A study on e-logistics service quality and its impact on customer satisfaction in e-commerce industry - KRISHNAMOORTHY, MR. D.; M, MS. SANDHIYA (The journal of contemporary issues in business and government, 2020)
The study is to identify the elogistics service quality dimensions and customer satisfaction on e-commerce the variables such as Information technology, convenient service reliability, responsiveness, assurance, empathy, tangibles. E-logistics is a new industry, in specific computerised arrival of worldwide business and strong network in e-commerce. The incorporation of technology with management of logistics has become a necessity for effective logistics management. The effect of models and activities of e-logistics include the organisation’s forward and reverse logistics functions. In today, The business climate is highly competitive, the importance of rapidly changing knowledge, and the importance of communication systems have been well known for overall success and in some situations even the sustainability of every operation in logistics. The study finds out the customer satisfaction on elogistics service providers by the e- commerce industry. The conclusion of the study states various factors that influence people to buy on e-commerce, such as customer satisfaction on responsiveness, assurance, empathy and tangible factors increase positive relationships but when the reliability factor decreases the customer satisfaction.